Discovery Learning: Upaya Meningkatkan Hasil Belajar IPA Materi Pencemaran pada Siswa di MTs Negeri 4 Gunungkidul - Isfi Muzari (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
This study aims to improve student learning outcomes by applying a discovery learning model. This study used the Action research method with two cycles. The subjects of the study were students of Class A Semester 2 of MTs Negeri 4 Gunungkidul SKS Service for the 2021/2022 academic year. The results of research in cycle I and cycle II showed an increase in student learning outcomes. In cycle I, the results of student attitude observations obtained an average score of 2.63 with completeness of 59.37%, increasing to 2.77 with completeness of 75% in cycle II. The results of observing students' skills obtained an average score of 65.93 with a completeness of 43.75% in cycle I, increasing to 70.2 with completeness of 75% in cycle II. The results of knowledge observation obtained an average value of 60 with a completeness of 43.8% in cycle I, increasing to 66.3 with completeness of 52.3% in cycle II. Based on data from observations of attitudes, skills, and knowledge assessments, it can be concluded that the results of science learning for grade A students in Semester 2 MTs Negeri 4 Gunungkidul SKS Services through the application of the discovery learning learning model have increased significantly.